The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/jha2.746
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised machine learning algorithms identify expected haemorrhage relationships but define unexplained coagulation profiles mapping to thrombotic phenotypes in hereditary haemorrhagic telangiectasia

Abstract: Hereditary haemorrhagic telangiectasia (HHT) can result in challenging anaemia and thrombosis phenotypes. Clinical presentations of HHT vary for relatives with identical casual mutations, suggesting other factors may modify severity. To examine objectively, we developed unsupervised machine learning algorithms to test whether haematological data at presentation could be categorised into sub‐groupings and fitted to known biological factors. With ethical approval, we examined 10 complete blood count (CBC) variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…All three individuals with variants 1 and 2 had clinically confirmed HHT. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 35 , 66 After identification of the SMAD4 variants, recruiting clinicians also reported SMAD4- compatible clinical phenotypes: The first-degree relatives with variant 2 had no other identified cause to HHT. They each experienced daily nosebleeds and had classical HHT telangiectasia, and one had pulmonary arteriovenous malformations requiring treatment and hemihypertrophy (left-right axis defect).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All three individuals with variants 1 and 2 had clinically confirmed HHT. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 35 , 66 After identification of the SMAD4 variants, recruiting clinicians also reported SMAD4- compatible clinical phenotypes: The first-degree relatives with variant 2 had no other identified cause to HHT. They each experienced daily nosebleeds and had classical HHT telangiectasia, and one had pulmonary arteriovenous malformations requiring treatment and hemihypertrophy (left-right axis defect).…”
Section: Resultsmentioning
confidence: 99%
“…For this, the annotated WGS files were retrieved for the 34 validation set DNAs where a causative variant had already been identified in known HHT genes through clinical pipelines. 13 , 14 , 15 , 16 , 34 , 35 Variant information was collected through unique variant IDs consisting of chromosome number, variant starting position, reference sequence, and altered sequence (e.g., chr1:111_C/TTT). To confirm that no two variants were represented by the same variant ID, the full list was compared to a set where only unique values were stored, and the two lists were identical.…”
Section: Methodsmentioning
confidence: 99%
“…Case notes were reviewed with ethical approval from the Hammersmith and Queen Charlotte’s and Chelsea Research Ethics Committee (LREC 2000/5764). Key findings in this cohort referring to individual clinical features corresponding to the respective genetic variants were published previously [ 57 , 71 , 72 , 85 ]. In the current study, we focused on the variants and the number of times each variant was reported.…”
Section: Methodsmentioning
confidence: 99%
“…Large prospectively-accrued series have identified environmental factors that contribute to more severe clinical manifestations once AVMs are present, particularly anaemia aggravating high-output states [ 49 ] and associated with earlier mortality [ 50 , 51 ]. Additionally, we have identified that in HHT, iron deficiency is associated with venous thromboemboli [ 52 ] and ischaemic strokes through pulmonary AVMs [ 53 ]; iron treatments can be associated with worsening nosebleeds in approximately 1 in 20 patients [ 54 , 55 ]; higher serum iron levels and intravenous iron treatments are independent risk factors for cerebral abscess due to pulmonary AVMs [ 56 ]; and, most recently, that unsupervised machine learning identifies relevant heterogeneity in blood indices [ 57 ]. Despite HHT clinical risks, recent European studies have shown that life expectancy is normal, or near-normal, in HHT [ 50 , 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation